2013
DOI: 10.1002/jts.21813
|View full text |Cite
|
Sign up to set email alerts
|

Mild Traumatic Brain Injury and Treatment Response in Prolonged Exposure for PTSD

Abstract: A proportion of U.S. veterans returning from Iraq and Afghanistan have experienced mild traumatic brain injury (mTBI), which is associated with increased risk for developing posttraumatic stress disorder (PTSD). Prolonged Exposure (PE) has proven effectiveness in the treatment of PTSD; however, some clinicians have reservations about using PE with individuals with a history of mTBI. We examined the impact of PE for veterans with PTSD and with or without a history of mTBI in a naturalistic sample of 51 veterans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(56 citation statements)
references
References 41 publications
5
51
0
Order By: Relevance
“…We used data only from individuals who had attended at least one session of PE. As with previous effectiveness studies (Goodson, Leftowitz, Helstrom, & Gawrysiak, ; Sripada et al., ), participants were considered to be therapy completers if they successfully negotiated at least eight sessions of PE. The demographic and clinical characteristics of the sample are summarized in Table .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used data only from individuals who had attended at least one session of PE. As with previous effectiveness studies (Goodson, Leftowitz, Helstrom, & Gawrysiak, ; Sripada et al., ), participants were considered to be therapy completers if they successfully negotiated at least eight sessions of PE. The demographic and clinical characteristics of the sample are summarized in Table .…”
Section: Methodsmentioning
confidence: 99%
“…Preliminary studies with veterans diagnosed with PTSD and mild TBI have suggested PE is safe, effective, and may yield additional benefits when implemented early in the TBI rehabilitation process (Sripada et al., ; Wolf, Strom, Kehle, & Eftekhari, ). These studies, however, did not evaluate the effectiveness of PE within a sample of veterans and active duty personnel with a range of TBI severity.…”
mentioning
confidence: 99%
“…In contrast to prior studies investigating the relation between mTBI and EBPs for PTSD, 19 the present study included a somewhat larger sample of patients with a history of TBI and LOC to more adequately test for differences in treatment response among those with and without TBI+LOC history. Although both groups demonstrated significant improvements in symptoms of PTSD and depression during the course of COPE, the control group evidenced significantly larger treatment improvements than the TBI+LOC-positive group.…”
Section: Discussionmentioning
confidence: 99%
“…In the only two studies to include a control group without TBI history, no differences were found between groups in outcomes for an EBP for PTSD. 19,21 However, the authors acknowledge that the sample size limited their ability to adequately test for group differences.…”
Section: Introductionmentioning
confidence: 99%
“…VHA is a leader in dissemination and implementation of evidence-based psychotherapies [47,48]. Multiple studies have demonstrated effectiveness with evidence-based psychotherapies for PTSD, TBI, and other mental health conditions [49].…”
Section: Veterans Health Administrationmentioning
confidence: 99%